A randomized controlled trial to pilot the efficacy of a computer-based intervention with elements of virtual reality and limited therapist assistance for the treatment of post-traumatic stress disorder - van Meggelen, Marieke; Morina, Nexhmedin; van der Heiden, Colin; Brinkman, Willem-Paul; Yocarini, Iris E.; Tielman, Myrthe L.; Rodenburg, Jan; van Ee, Elisa; van Schie, Kevin; Broekman, Marijke E.; Franken, Ingmar H. A. (Frontiers in Digital Health, 2022)
Although well-established therapies exist for post-traumatic stress disorder (PTSD), barriers to seek mental health care are high. Technology-based interventions may play a role in improving the reach of efforts to treat, especially when therapist availability is low. The goal of the current randomized controlled trial was to pilot the efficacy of a computer-based trauma intervention with elements of virtual reality (VR; 3MR system) and limited therapist involvement for the treatment of PTSD in a childhood sexual abuse (CSA) and war veteran sample and to compare this to “treatment as usual” (TAU). TAU consisted of evidence-based approaches such as imaginal exposure, EMDR, or narrative exposure therapy. A total of 44 patients with PTSD were included and randomly assigned to 12 sessions of 3MR intervention or TAU (completer n 3MR = 12, TAU = 18). Several measures (PCL-5, BDI-II, OQ-45-2, and the M.I.N.I. 5.0.0.) were administered to measure symptoms of PTSD and depression and scores of overall well-being at pre, post, and a three-month follow-up measurement. Analyses suggest that symptoms of PTSD and depression in the 3MR condition decreased, and overall well-being increased between pre and post measurements. Results did not indicate any clear differences between the treatment conditions over time which suggests that treatment gains of the 3MR intervention seem no less than those of TAU. Finally, both treatment conditions produced similar remission rates of PTSD and depression. Therefore, the 3MR intervention could possibly constitute an appropriate treatment alternative. The small sample size as well as evident drop-out rates in the 3MR condition (45%) do warrant further research. The procedures of this study were approved by the Medical Ethical Research Committee (MERC) of the Erasmus Medical Center in Rotterdam (MEC-NL46279.078.13) and pre-registered via ClinicalTrials.gov (Protocol Record CI1-12-S028-1).